PROPERTIES OF THE PARABOLA IN DIFFERENT COORDINATE SYSTEMS - Norieva , Aziza Jasur qizi (Educational Research in Universal Sciences, 2023)
This article presents the properties of second-order lines in different coordinate systems, and the article can be used by young students studying analytical geometry in higher education institutions.